Langgam Makassar: the adaptation of keroncong to local music in Makassar - Adiatma Hudzaifah; Zulkarnain Mistortoify (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
The musical landscape of Makassar features a unique variant of keroncong known as "Langgam Makassar." Faced with limited references to keroncong before Indonesia's independence, musicians in Makassar encountered a dilemma that prompted inventive solutions in the development of keroncong. This led to the emergence of Langgam Makassar as a distinct variant, undergoing a process of adaptation to the local music scene. The research aims to illustrate and explore key aspects of Langgam Makassar, encompassing musicological, historical, and societal dimensions. The methodology employed in this study is an ethnomusicological approach involving direct observation of Langgam Makassar practices and performances. The findings were validated through interviews with Langgam Makassar musicians, recordings, and document analysis. This method offers an understanding of music within its societal context, exploring the reasons why keroncong in Makassar diverges and evolves into Langgam Makassar. The results demonstrate that Langgam Makassar is a product of the creativity of Makassar musicians who, despite limitations, successfully developed keroncong by incorporating elements from local musical traditions such as kelong, parambang, and losquin. These efforts contribute to the distinctive features of Langgam Makassar, establishing it as a novel variant of keroncong.